2014
DOI: 10.1242/jcs.158303
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin regulates centrosome positioning by promoting acto-myosin cortical tension in C. elegans embryos

Abstract: Regulation of centrosome and spindle positioning is crucial for spatial cell division control. The one-cell Caenorhabditis elegans embryo has proven attractive for dissecting the mechanisms underlying centrosome and spindle positioning in a metazoan organism. Previous work revealed that these processes rely on an evolutionarily conserved force generator complex located at the cell cortex. This complex anchors the motor protein dynein, thus allowing cortical pulling forces to be exerted on astral microtubules e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…We show that AP-patterning across the whole tissue, through the planar polarisation of Myosin II, biases the metaphase spindle towards AP for all mitotic cells. This generalises our previous finding that strongly Myosin II-enriched PSBs attract and stabilise spindle ends suggesting that Myosin II could be directly involved in attracting the spindle, possibly through increased cortex stiffness (Spiro et al, 2014). AP-patterning straddles the whole DV circumference of the embryo (Irvine and Wieschaus, 1994) so that even the ME domain has polarised Myosin II, driving AP-oriented division in these isotropic cells.…”
Section: Control Of Ocd By Ap-patterningsupporting
confidence: 85%
“…We show that AP-patterning across the whole tissue, through the planar polarisation of Myosin II, biases the metaphase spindle towards AP for all mitotic cells. This generalises our previous finding that strongly Myosin II-enriched PSBs attract and stabilise spindle ends suggesting that Myosin II could be directly involved in attracting the spindle, possibly through increased cortex stiffness (Spiro et al, 2014). AP-patterning straddles the whole DV circumference of the embryo (Irvine and Wieschaus, 1994) so that even the ME domain has polarised Myosin II, driving AP-oriented division in these isotropic cells.…”
Section: Control Of Ocd By Ap-patterningsupporting
confidence: 85%
“…A transcriptome‐wide binding study identified few such mRNAs (for example, SEC6 [Secretory 6; a subunit of the exocyst complex], SEC13, SMY2 [Suppressor of Myo2‐66 2; involved in COPII vesicle formation], and SWA2 [Synthetic lethal With Arf1 2; involved in the uncoating of clathrin‐coated vesicles] binding to Scd6 (Tsvetanova, Klass, Salzman, & Brown, ). Strikingly, it was reported in worms that CAR‐1 depletion causes a decrease in CHC‐1 protein levels and knockdown of CAR‐1 leads to similar phenotypes as CHC‐1 knockdown (Spiro et al, ). The mechanism by which CAR‐1 affects CHC‐1 levels is unknown.…”
Section: Functions and Interactions Of Scd6mentioning
confidence: 99%
“…In C. elegans embryos, it has been shown that a direct interaction between the conserved MT bundler protein regulator of cytokinesis 1 (PRC1) and centralspindlin is important for the mechanical robustness of the central spindle, which experiences considerable tensile forces (Lee et al, ). In C. elegans embryo cytokinesis, it has been shown that clathrin heavy chain 1 (CHC‐1) promotes actomyosin cortical tension, thus stabilizing CR position (Spiro et al, ).…”
Section: Cell Shape Tension and Mt‐independent Control Of Cytokinetmentioning
confidence: 99%